HUBUNGAN STADIUM ULKUS DENGAN KUALITAS HIDUP PADA PASIEN DM TIPE II - Linda ' Mairiyani; Siti ' Rahmalia; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract DiabetesMellitus(DM) is a group of diseasescharacterizedbyhyperglycemiaresulting fromdefectsin insulin secretion, insulin actionor both. One of thecomplications ofdiabetes isperipheral neuropathyin the form ofulcers that influence of quality of life patient's. The aim of this research is to determine the relationship of diabetic ulcers stage with quality of life in patients with type 2 of diabetes mellitus. This research using with descriptive correlation and design using with crosssectional approach. The research was conducted at the RSUD Petala Bumi Pekanbaru on 30 respondents diabetic ulcers using accidental sampling technique with inclusion criteria. The descriptive analyzed was Kolmogorov-Smirnov. The results showed p <0,05 which means there is a relationship between diabetic ulcer stage with quality of life in patients from type 2 of diabetes mellitus with p value = 0.000. This research is expected to be a guide in improving the quality of life of diabetic patients with diabetic ulcers. Keywords: DM, diabetic ulcers, quality of life